2020
DOI: 10.34172/jlms.2020.26
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Surface Treatment With Er:YAG and CO2 Lasers on Shear Bond Strength of Polyether Ether Ketone to Composite Resin Veneers

Abstract: Introduction: Polyether ether ketone (PEEK) has low surface energy and high resistance to chemical surface treatments. Therefore, different surface treatments such as laser conditioning should be investigated. There is a gap of information regarding the efficacy of laser irradiation in the surface treatment of PEEK, and the efficacy of several laser types needs to be evaluated for this purpose. This study aimed to assess the effect of surface treatment with erbium-doped yttrium aluminum garnet (Er:YAG) and car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 53 publications
3
17
0
Order By: Relevance
“…For example, CO 2 laser treatment did not significantly enhance the SBS of tested PEEK (unfilled PEEK, carbon reinforced PEEK and glass reinforced PEEK) to the resin cement, as shown by Henriques et al [ 125 ]. Similar results that CO 2 laser treatment had little effect on the inertness and bond strength of the PEEK surface were indicated in another study [ 126 ]. Additionally, in that study, the use of Erbium-doped yttrium aluminum garnet (Er: YAG) laser irradiation provided the highest SBS; thus, it could be a feasible approach for improving the adhesive properties of PEEK to the veneers.…”
Section: Adhesion Of Peek To Dental Compositessupporting
confidence: 88%
“…For example, CO 2 laser treatment did not significantly enhance the SBS of tested PEEK (unfilled PEEK, carbon reinforced PEEK and glass reinforced PEEK) to the resin cement, as shown by Henriques et al [ 125 ]. Similar results that CO 2 laser treatment had little effect on the inertness and bond strength of the PEEK surface were indicated in another study [ 126 ]. Additionally, in that study, the use of Erbium-doped yttrium aluminum garnet (Er: YAG) laser irradiation provided the highest SBS; thus, it could be a feasible approach for improving the adhesive properties of PEEK to the veneers.…”
Section: Adhesion Of Peek To Dental Compositessupporting
confidence: 88%
“…Shear bond strength tests have indicated that the stress distribution of the bonding interface is non‐homogeneous [54,55] In addition, shear bond strength tests do not require specimen trimming and are easier to conduct than tensile tests [53]. Moreover, shear bond strength tests can simulate the load exerted on a material in oral conditions [56]. However, in vitro experimental results need to be interpreted with caution because the actual clinical environment is more complex [56].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, shear bond strength tests can simulate the load exerted on a material in oral conditions [56]. However, in vitro experimental results need to be interpreted with caution because the actual clinical environment is more complex [56]. Thus, in the present study, a shear bond strength test was used to evaluate the bond strength of the zirconia interface.…”
Section: Discussionmentioning
confidence: 99%
“…After micro-second laser treatment, the wettability of surface turned to hydrophobic while the oxygen content was slightly changed, which has also been proved in other previous work. 26,27,38 Based on the results shown in Figures 1-4, it was indicated that the increase in the single lap shear strength was mainly due to the microscale porous surface texturing. On the other hand, nanosecond laser treatment was expected to improve a chemical adhesion on the PEEK/CF surface by forming C=O and O-C=O functional groups.…”
Section: Pulse Widthmentioning
confidence: 98%
“…Tsuka et al 26 proved that the laser treatment greatly enhanced the chemical adhesion and mechanical interlocking of PEEK surface to improve the shear bond strength. Jahandideh et al 27 found that the Er:YAG and CO 2 laser treatments can increase the bonding strength of PEEK to composite resin veneers and the Er:YAG laser seemed to be more effective for improving adhesive properties of PEEK.…”
Section: Introductionmentioning
confidence: 99%